2020
DOI: 10.1002/adma.202002620
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Alignment of Supramolecular Columns by Photothermal Laser Writing

Abstract: Controlling the orientation of highly periodic supramolecular structures of small feature size (<5 nm) is the first step for potential applications in optoelectronics, membranes, and template synthesis. A new method, namely, laser photothermal writing, is introduced to direct the orientation of supramolecular columns over a large area. Supramolecular columns consisting of taper‐shaped molecules with long aliphatic tail groups are aligned by a thermal gradient, which is induced by exposing a near‐infrared laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Figure a illustrates the overall process for aligning the supramolecular columns on a faceted sapphire surface. We synthesized supramolecular columns consisting of taper-shaped molecules (Figure b), and these molecules self-assembled to form a stable columnar phase at room temperature after cooling from the isotropic temperature (87 °C). ,,, These taper-shaped molecules with long aliphatic tail groups can easily be spin-cast to form a thin-film geometry without any surface modifications.…”
Section: Resultsmentioning
confidence: 99%
“…Figure a illustrates the overall process for aligning the supramolecular columns on a faceted sapphire surface. We synthesized supramolecular columns consisting of taper-shaped molecules (Figure b), and these molecules self-assembled to form a stable columnar phase at room temperature after cooling from the isotropic temperature (87 °C). ,,, These taper-shaped molecules with long aliphatic tail groups can easily be spin-cast to form a thin-film geometry without any surface modifications.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we report a simple one-pot approach to produce liquid Ga-based core–shell NPs, in which liquid GaNPs serve as a sacrificial reductive core and are coated with a layer of densely packed reduced graphene oxide (RGO) nanosheets (Figure a). To enhance the photothermal conversion efficiency of liquid GaNPs, a graphene nanosheet shell is utilized as a strong light absorber and photothermal conversion center in this work. , Conventional methods to synthesize NPs with a metallic core–graphene shell require the surface modification of a rigid core with positively charged functional groups as the first step to attract negatively charged graphene oxide (GO) sheets. , RGO forms by chemical reduction of the GO sheets by, for example, the addition of hydrazine hydrate , or thermal treatment with a H 2 –Ar gas mixture. , Such relatively complicated synthetic methods may limit the scale-up of the product, and most surfactants in the reactions are hard to be removed and toxic to cells, , which further brings safety hazards in the field of biological-related applications. Micro-sized LM droplets assembled with reduced GO sheets was developed by Baharfar et al Using the strong galvanic interaction between LM and GO, the core–shell structure was synthesized and applied to selective biosensing of dopamine, which is one of the most important neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the photothermal conversion efficiency of liquid GaNPs, a graphene nanosheet shell is utilized as a strong light absorber and photothermal conversion center in this work. 30,31 Conventional methods to synthesize NPs with a metallic core− graphene shell require the surface modification of a rigid core with positively charged functional groups as the first step to attract negatively charged graphene oxide (GO) sheets. 32,33 RGO forms by chemical reduction of the GO sheets by, for example, the addition of hydrazine hydrate 32,34 or thermal treatment with a H 2 −Ar gas mixture.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 5 , 6 In recent years, laser marking technology has emerged as a new type of printing technology that uses high-energy lasers to mark the surface of materials to form patterns, text, crystalline and self-assembly structures, and morphology. 6 12 For example, Park et al 13 reported the laser-directed supramolecular assembly of sub-5 nm columnar structures with adjustable orientation control. The high energy of the laser causes the matrix resin to be heated and carbonized, forming a clear pattern 14 , 15 of carbonization and blackening on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Due to excellent heat resistance, high chemical stability, resistant ability to most acid and alkali corrosions, and good processability, PP and its composite materials have been widely used in automobiles, packaging, membrane separation and pipelines, and other fields. Generally, the surface of PP products needs to be marked with patterns and texts such as two-dimensional (2D) codes and serial numbers to indicate the production date, company logo, the product expiration date, and anticounterfeiting functions. Usually, ink printing is used to produce these marks on the surface of the material, but there is the use of toxic and harmful reagents, the process flow is complicated, and there are serious environmental pollution problems. , In recent years, laser marking technology has emerged as a new type of printing technology that uses high-energy lasers to mark the surface of materials to form patterns, text, crystalline and self-assembly structures, and morphology. For example, Park et al reported the laser-directed supramolecular assembly of sub-5 nm columnar structures with adjustable orientation control. The high energy of the laser causes the matrix resin to be heated and carbonized, forming a clear pattern , of carbonization and blackening on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%